Detection of antibiotic resistance of the phylogenetic group E among E. coli bacteria isolated from diarrheal cases in children under five years - Alshwaikh, Rana Mujahid; Abed Al-Azzawi, Shahla Najim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
From 50 stool samples collected from children with diarrhea of both sexes who visited various hospitals in Baghdad, 26 isolates of E.coli were found to belong to the phylogenetic group E. The findings revealed that the percentage of E.coli for thephylogenetic group E is (52%) , making it the dominant group among the other phylogenetic groups. The findings demonstrated that 100% of the E.coli isolates from phylogenetic group E are resistant to penicillin, and only 15% are resistant to imipenem. Multi-drug resistance (MDR) was found to be 15%, while XDR reached 85%. The results of thephylogenetic group for the remaining species of isolates in this study were group A (2/50 and by 4%), group B2 (1/50 and by 2% ),group C (12/50 and by 24%), group D (6/50 and by 12%), group F (3/50 and by 6%), group B1 by 0%, and group Clade 1 by (0%).